Petrology, geochemisty and isotopie characteristics of the shoshonitic plutonic rocks from Maronia area, West Thrace, Greece - PAPADOPOULOU, L.; CHRISTOFIDES, G.; BRÖCKER, M.; KORONEOS, Α.; SOLDATOS, T.; ELEFTHERIADIS, G. (Bulletin of the Geological Society of Greece, 2001)
The Maronia pluton, a high-K intrusion in the Circum Rhodope Belt, comprises gabbro to monzonite to granite having pyroxene, biotite and less olivine and amphibole. Three rock groups have been recognised: a basic, an intermediate and an acid. Major, trace and REE geochemistry as well as Sr and Ο isotopes support a genetic relation between the basic and the intermediate group but not between them and the acid group. An AFC process with a carbonate assimilant or an MFC process, where the basic end-member is represented by the less evolved samples, and the acid end-member by more evolved samples having Sr isotopes higher than those in the acid group, is suggested for the evolution of the basic-intermediate group. The basic-intermediate group originates from a lithospheric mantle while the acid group probably from a low-Sr isotopes crustal melt.